Gastropod Community Structure in Seagrass Ecosystems in North Minahasa Ganges Waters - Sitanggang, Gorga Renaldi; Rangan, Jety K.; Moningkey, Rudy D.; Lalita, Jans D.J; Manu, Gaspar D.; Schaduw, Joshian N. W (Sam Ratulangi University, 2021)
The purpose of this study was to determine the types of gastropods in the seagrass ecosystem in the waters of Gangga I Village, North Minahasa Regency through Species Density, Relative Density, Diversity and Dominance in the waters of Gangga I Village, North Minahasa Regency. The results of the study obtained 126 individuals consisting of 13 species (7 genera) from 7 families (3 orders). The results of the analysis of the gastropod community structure showed that the highest species density value was at point 1 of 1.67 ind/m², followed by point 2 of 1.43 ind/m² and the lowest was at point 3 of 1.20 ind/m². The low density of gastropods at the 3 points is assumed to be caused by the environmental conditions in which they live, food sources, and fishing activities carried out by the local community. The relative density value of species with the highest percentage is at point 3, namely, the species Nassarius albescens 0.167% and the species with the lowest percentage is at point 1, namely the species Xenoturris millepunctata 0.020%. The diversity index value which includes the high criteria is at point 1 of 3.25, while the diversity value which includes the medium criteria is at point 2 of 2.87 and point 3 of 2.42. The dominance value obtained from the analysis ranges from C = 0.09 to 0.12 which is classified as low. while the value of diversity which includes the medium criteria is at point 2 of 2.87 and point 3 of 2.42. The dominance value obtained from the analysis ranges from C = 0.09 to 0.12 which is classified as low. while the value of diversity which includes the medium criteria is at point 2 of 2.87 and point 3 of 2.42. The dominance value obtained from the analysis ranges from C = 0.09 to 0.12 which is classified as low.Keywords; Density; Diversity; Dominance; Environmental. AbstrakTujuan dari penelitian ini adalah untuk mengetahui jenis-jenis Gastropda di Ekosistem lamun perairan desa Gangga I, Kabupaten Minahasa Utara melalui: Kepadatan Spesies, Kepadatan Relatif, Keanekaragaman dan Dominansi di perairan Desa Gangga I Kabupaten Minahasa Utara. Dari hasil penelitian, diperoleh 126 individu yang terdiri atas 13 spesies (7 genera) dari 7 famili (3 ordo). Hasil analisis struktur komunitas gastropoda diperoleh nilai kepadatan spesies tertinggi pada titik 1 sebesar 1,67 ind/m², diikuti titik 2 sebesar 1,43 ind/m² dan yang terendah ada pada titik 3 sebesar 1,20 ind/m². Rendahnya kepadatan gastropoda pada ke 3 titik diasumsikan disebabkan oleh kondisi lingkungan tempat hidupnya, sumber makanan dan aktivitas perikanan yang dilakukan masyarakat setempat. Adapun Nilai kepadatan relatif jenis dengan persentase tertinggi ada pada titik 3, yaitu spesies Nassarius albescens 0,167% dan spesies dengan persentase terendah ada pada titik 1, yaitu spesies Xenoturris millepunctata 0,020%. Nilai indeks keanekaragaman yang termasuk kriteria tinggi terdapat pada titik 1 sebesar 3,25, sedangkan nilai keanekaragaman yang termasuk kriteria sedang terdapat pada titik 2 sebesar 2,87 dan titik 3 sebesar 2,42. Nilai dominansi yang diperoleh dari analisis berkisar C = 0,09 sampai dengan 0,12 yang tergolong rendah.Kata kunci; Kepadatan; Keanekaragaman; Dominansi; Lingkungan